Diseño de una máquina inyectora de termoplásticos de baja y alta densida. - Martínez Garcés, Luis Daniel (2018)
Injection molding allows the manufacture a wide variety of parts with unique advantages, such as fast manufacturing and high production levels at low costs. High precision machined equipment and strict manufacturing controls allow the raw materials to be transformed into a finished product, in exact shapes with high quality standards and very adaptable to customer necessities to make the investment profitable. This research is focused on the machine design for the injection of high and low density thermoplastic materials with an injection mass of 200 to 300 grams of medium production capacity, through the analysis of the part to be produced and the injection process by the finite element method, using FEM-FEA simulation software, where the simulation outline conditions are set, the ideal parameters are obtained of the injection process variables that serve as starting data for the machine design. The element tested is a plastic gear for conveyor belts, where the filling process was analyzed to determine the problems that directly affect the product quality. Mechanical tensioning strain were determined: strain, bending and safety factor of the injected element it means a structural safety test to ensure the service element life. The raw material to be processed by the machine is NYLON PA6 for high-density thermoplastics and LLDPE IN34 for low-density thermoplastics, which must meet the technical and economic requirements and availability in the local and national market. Finally, a functional and cost machine analysis was carried out where it was compared with the existing ones in the market in order to determine the acquisition costs and the production capacity.